Assessment of the use of Participatory Integrated Climate Services for Agriculture (PICSA) approach by farmers to manage climate risk in Mali and Senegal - Dayamba, Sidzabda Djibril; Ky-Dembélé, Catherine; Bayala, Jules; Dorward, Peter; Clarkson, Graham; Sanogo, Diaminatou; Mamadou, Lamine Diop; Traoré, Issa; Diakite, Adama; Nenkam, Andree M.; Binam, Joachim N.; Ouédraogo, Mathieu; et al. (Elsevier, 2018)
Recently, a new approach to extension and climate information services, namely Participatory Integrated Climate Services for Agriculture (PICSA) has been developed. PICSA makes use of historical climate records, participatory decision-making tools and forecasts to help farmers identify and better plan livelihood options that are suited to local climate features and farmers’ own circumstances. This approach was implemented in 2016 in two sites in Senegal and Mali, with 57 and 47 farmers, respectively. At the end of the growing season, these farmers were surveyed to explore their perceptions on the use of the approach. In Senegal and Mali, respectively 97% and 76% of the respondents found the approach ‘very useful’. The approach enabled farmers to make strategic plans long before the season, based on their improved knowledge of local climate features. Moreover, evidence demonstrates that PICSA stimulated farmers to consider and then implement a range of innovations which included: (i) changes in timing of activities such as sowing dates, (ii) implementing soil and water management practices, (iii) selection of crop varieties, (iv) fertiliser management and (v) adaptation of plans for the season (farm size, etc.) to the actual resources available to them. The study also demonstrated the potential of farmer-to-farmer extension in scaling up the approach, which is of great interest especially in the current context of limited extension services in the West African region.